Kajian Proporsi Wajah Wayang Potehi Perempuan di Gudo, Jombang dengan Proporsi Rasio Emas - Hasprita Restiamangastuti Boru Mangunsong; Djuli Djatiprambudi (Universitas Negeri Medan, 2021)
Since long time ago, people of the archipelago have interacted with various foreign nations and it led to the integration of local cultures and migrant cultures and resulting some new cultures. One of them is Potehi Puppet, a puppetry originated from China then developed in Java. The purpose of this study is to find out and describe a face proportion of female character of Potehi Puppet in Gudo, Jombang. The method that used is quantitative research by measuring some female characters of Potehi Puppet using Golden Proportion theory and calculate the mean of the measuring result also interview to the chairman, Toni and puppeteer of Hok Ho An (Potehi group in Gudo), Sonny and direct observation. Golden Proportion theory is not used to judge but used as tool to find out the mean of face proportion measuring. The result showed that there is an acculturation between Chinese and Javanese culture in visual, language, story, character and their characteristics and the artists behind Potehi Puppet. Potehi Puppet characters are distinguished majority by symbols on their clothes and accessories especially female characters. Some characteristics of female Potehi Puppet that Toni’s engravers made which quite different with female Potehi Puppet that made in China. It shows that artists background (Javanese) influences their Potehi Puppet work.